2016
DOI: 10.1155/2016/8192323
|View full text |Cite
|
Sign up to set email alerts
|

Mollicutes/HIV Coinfection and the Development of AIDS: Still Far from a Definitive Response

Abstract: Background. Mycoplasmas are known to cause various infections in humans, mainly in the respiratory and urogenital tracts. The different species are usually host-specific and cause diseases in well-defined sites. New species have been isolated, including those from HIV-infected persons. Summary. Its in vitro properties, combined with clinical findings, have led to the hypothesis that these microorganisms may act as cofactors of HIV in AIDS development. Even today this point of view is quite polemic among infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Previous studies reported similar Ureaplasma spp. colonization patterns in the genitourinary tract in HIV positive individuals, (Martinelli et al, 1999;Wang et al, 2012;de Cordova et al, 2016). This is, at least to our knowledge, the first study to evaluate the extent of anal Ureaplasma spp.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Previous studies reported similar Ureaplasma spp. colonization patterns in the genitourinary tract in HIV positive individuals, (Martinelli et al, 1999;Wang et al, 2012;de Cordova et al, 2016). This is, at least to our knowledge, the first study to evaluate the extent of anal Ureaplasma spp.…”
Section: Discussionmentioning
confidence: 83%
“…Among women they are responsible mainly for nongonococcal urethritis and bacterial vaginosis. Serious complications may occur during pregnancy and after delivery with manifestations like chorioamnionitis, post-partum and postabortal fever, congenital pneumonia, neonatal bacteremia and neonatal abscesses (Zhang et al, 2014;de Cordova et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Genital mycoplasmas and ureaplasmas belong to the Mycoplasmataceae family and Mollicutes class. 4,5 They represent a group of atypical wall-less bacteria and are the smallest self-replicating organisms, both in genome size and cellular dimensions. 4,5 The introduction of nucleic acid amplification tests (NAATs) has improved the knowledge regarding the epidemiology of these microorganisms and allowed to distinguish between species.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 They represent a group of atypical wall-less bacteria and are the smallest self-replicating organisms, both in genome size and cellular dimensions. 4,5 The introduction of nucleic acid amplification tests (NAATs) has improved the knowledge regarding the epidemiology of these microorganisms and allowed to distinguish between species. 3,6 As a result of sexual intercourse, genital mycoplasmas and ureaplasmas can be isolated from the genitourinary tract of both males and females.…”
Section: Introductionmentioning
confidence: 99%